Evaluation of a vaccine passport to improve vaccine coverage in people living with HIV. (October 2018) - Chadwick, DR; Corbett, K; Mann, S; Teruzzi, B; Horner, S
An increased risk of vaccine-preventable infections (VPIs) is seen in people living with HIV (PLWH), and current vaccine coverage and immunity is variable. Vaccine passports have the potential to improve vaccine coverage. The objective was to assess how successful a vaccine passport was in improving vaccine coverage in PLWH. Baseline immunity to VPIs was established in PLWH attending a single HIV clinic and vaccinations required were determined based on the BHIVA Vaccination Guidelines (2015). The passport was completed and the PLWH informed about additional vaccines they should obtain from primary care. After 6–9 months the passport was reviewed including confirmation if vaccines were given. PLWH satisfaction with the system was evaluated by a survey. Seventy-three PLWH provided sufficient data for analysis. At baseline significant proportions of PLWH were not immune/unvaccinated to the main VPIs, especially human papillomavirus, pneumococcus and measles. After the passport was applied immunity improved significantly (56% overall, p < 0.01) for most VPIs; however, full coverage was not achieved. The system was popular with PLWH. The passport was successful in increasing vaccination coverage although full or near-full coverage was not achieved. A more successful service would probably be achieved by commissioning English HIV clinics to provide all vaccines.